Under the Spell of Distant Landscapes: On the Lives and Work of a Few Famous Hungarian Travellers and Explorers after 1945 – an Introduction to the Topic for English-Speaking Readers - Zsolt András Udvarvölgyi (Studia Historiae Scientiarum, 2023)
All travellers and explorers have always had the desire and the ambition to discover, for different reasons and motivations, remote and unknown lands. Hungarian travellers and explorers are no exception here. Eminent Hungarian Orientalists, archaeologists, geographers, as well as anthropologists, geologists, zoologists and botanists, and other brave and adventurous scientists, have become justly recognised in recent centuries, even worldwide, for their oeuvres and their scientific achievements.